An empirical study on the effect of non-performing loans and fraud on the financial performance of tier 1 deposit money banks in Nigeria - Adedipe, Oluwaseyi; Oluwamuye, Abayomi (Journal of Accounting, Business and Finance Research, 2025)
The study aimed at evaluating the extent to which non-performing loans and fraud affect the financial performance of Tier 1 deposit money banks in Nigeria. The study made use of secondary data which are gotten from central bank statistical bulletin 2025. The study made use of the multiple regression method for the analysis. The study therefore concluded that there is a significant relationship between fraud cases, non-performing loans and financial performance of tier 1 deposit money banks in Nigeria. The study recommends that Tier 1 banks should enhance their risk management frameworks to effectively address non-performing loans and fraud. This includes implementing stricter credit controls, conducting regular loan portfolio reviews, and investing in advanced fraud detection technologies.